Renaissance : the blood and the beauty [videorecording (DVD)] - Dance, Charles; Mann, Eddie; Glynn, Jonny (BBC, 2025)
The story of how the greatest art works of all time were born of war and bloodshed, as rival artists Michelangelo, Leonardo and Raphael compete to craft beauty from chaos.